Fostering Knowledge Sharing Culture in Pesantren: The Charismatic Leadership Perspective - Fatrilia Rasyi Radita; Gunawan Santoso; Ferdinal Lafendry (International Journal of Management and Economic Research (IJOMER), 2024)
The purpose of this study is to investigate how psychological safety atmosphere and tacit knowledge exchange are impacted by charismatic leadership. The crucial function of psychological safety climate as a mediator factor between charismatic leadership and tacit knowledge sharing is also examined in this study. This study used 61 samples of ustadz/ustadzah from a Banten pesantren using a straightforward random sampling technique. The study's findings suggest that the atmosphere of psychological security and tacit information sharing is significantly influenced directly by charismatic leadership. Likewise, sharing of tacit knowledge is directly impacted by the psychological security environment in a big way. Additionally, through the mediation of a psychological safety atmosphere, this study finds evidence of the large indirect impact that charismatic leadership has on the sharing of tacit information. Accordingly, in this research paradigm, the psychological safety atmosphere serves as a partial mediator.